Suspensionplasty using Anchors and Non-Absorbable Sutures for Rhizarthrosis - Ribak, Samuel; de Carvalho, Giovanna Colnago Antunes; de Oliveira, Ricardo Kaempf (Revista Iberoamericana de Cirugía de la Mano, 2018)
Objective To analyze the clinical and radiographic results of patients with rhizarthrosis who underwent surgical treatment for resection of the trapezium bone using a fixation system with anchors and a non-absorbable suture.Methods Fifteen patients with a mean age of 60.26 years old were studied. Fourteen patients had type III rhizarthrosis and 1 had type II rhizarthrosis, according to the Eaton-Littler classification. Data on the professional activity, affected side, and hand dominance were collected and evaluated for the presence of pain, degree of joint movement of the radial abduction of the thumb, opposition, and palmar grip strength. The upper limb function was assessed using the Quick Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. The patients were subjected to pre and postoperative radiographic examinations, by which the scaphoid-first metacarpal height was measured using the oblique view of the hand. Suspensionplasty by fixation was then performed using a system of two 2.0 mm threaded bone anchors and a 2.0 mm Ethibond (Ethicon, Inc., Somerville, NJ, USA) suture wire. Finally, the trapezium bone was resected.Results The mean follow-up duration was 21.50 ± 5.02 months. The patients showed a mean score of 1.6 in the final evaluation using the visual analog scale. The degree of joint movement of the abduction of the thumb was on average 61.67° postoperatively and 59.73° preoperatively. There was an improvement in thumb opposition and a significant improvement in the upper limb function, as assessed using the Quick DASH method. The scaphoid-first metacarpal height had a proximal migration of ∼ 50% in the postoperative radiographs. The mean time to return to daily living activities was 20.7 days, 24.7 days to practical life activities, and 101.3 days to work activities. There was no correlation between the level of professional activity and the incidence of the disease.Conclusions Trapeziectomy and suspensionplasty, using an anchorage system and a non-absorbable suture, shows a significant improvement in pain, opposition, and function of the affected upper limb, and is efficient for the surgical treatment of rhizarthrosis. It allows for a rapid return to daily living activities with a low risk for complications.
Keywords: Osteoarthritis; trapezometacarpal joint; trapeziectomy; suspensionplasty; anchorage